2017
DOI: 10.3847/1538-3881/aa5c8a
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Upper Limit on the Interstellar Number Density of Asteroids and Comets

Abstract: We derived 90% confidence limits (CLs) on the interstellar number density (r IS CL ) of interstellar objects (ISOs; comets and asteroids) as a function of the slope of their size-frequency distribution (SFD) and limiting absolute magnitude. To account for gravitational focusing, we first generated a quasi-realistic ISO population to~750 au from the Sun and propagated it forward in time to generate a steady state population of ISOs with heliocentric distance <50 au. We then simulated the detection of the synthe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
126
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 49 publications
9
126
3
Order By: Relevance
“…Most moving objects detected by LSST will be "unremarkable" asteroids in the main belt, but this very large and deep survey (20,000 deg 2 surveyed to r magnitude 24.5 repeatedly over ten years) naturally has the possibility to discover unusual objects in all areas of astrophysics. Several authors have studied the detectability of interstellar interlopers in LSST data (Moro-Martín et al 2009;Cook et al 2016;Engelhardt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most moving objects detected by LSST will be "unremarkable" asteroids in the main belt, but this very large and deep survey (20,000 deg 2 surveyed to r magnitude 24.5 repeatedly over ten years) naturally has the possibility to discover unusual objects in all areas of astrophysics. Several authors have studied the detectability of interstellar interlopers in LSST data (Moro-Martín et al 2009;Cook et al 2016;Engelhardt et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical existence of ejectoids has been long proposed (e.g., Sekanina 1976), with various authors using non-detections to place upper limits on the population (McGlynn & Chapman 1989;Sen & Rama 1993;Engelhardt et al 2017). Jewitt (2003) and Francis (2005) suggested that PanSTARRS could detect an interstellar object, if the number density was great enough.…”
mentioning
confidence: 99%
“…Next generation time-domain sky surveys, such as the Large Synoptic Sky Survey (Tyson 2002), will provide deeper coverage over wider areas, hopefully revealing more objects like 'Oumuamua (Cook et al 2016;Engelhardt et al 2017). This will provide better estimates of the number density and size distribution of interstellar objects which are presently poorly constrained.…”
Section: <´-( )mentioning
confidence: 99%
“…In 19 years of digital-camera all-sky surveying, it is the first definitively interstellar, decameter-scale object to be found. The earlier lack of detections has implied a low density of interstellar planetesimals (Francis 2005;Cook et al 2016;Engelhardt et al 2017). Several Earth masses of ejected bodies are expected per star during planetary formation and migration (e.g., Levison et al 2010;Barclay et al 2017).…”
Section: Introductionmentioning
confidence: 99%